'Being a team, working together, and being kind': Primary students' perspectives of cooperative learning's contribution to their social and emotional learning. (4th March 2021) - Dyson, Ben; Howley, Donal; Shen, Yanhua
ABSTRACT: Background/purpose: It has been suggested that cooperative learning (CL) is a model-based practice which can develop students' social and emotional learning (SEL) competencies in physical education (PE) (Casey, Ashley, and Javier Fernandez-Rio. 2019. "Cooperative Learning and the Affective Domain." Journal of Physical Education, Recreation & Dance 90 (3): 12–17). The purpose of this study was to investigate how the pedagogical practice of CL contributed to SEL outcomes in PE from a student perspective in Aotearoa New Zealand (NZ) primary schools. Participants and settings: Students at four primary schools participated in the study as part of a larger research study on school-based, teacher-driven professional learning groups supporting the implementation of CL in PE. Research design: This research adopted a case study design (Stake, Robert E. 2006. Multiple Case Study Analysis . New York: Guilford) drawing on qualitative research methods utilizing student interviews and field notes over two years (Miles, Matthew B., A. Michael Huberman, and Johnny Saldaña. 2014. Qualitative Data Analysis: A Methods Sourcebook . Thousand Oaks, CA: SAGE). One researcher was assigned to each school as a critical friend to each teacher. Teachers used CL structures, with students placed in small groups of 3–5, given different roles, and operating as a team to complete a task or play in a modified game (Dyson, Ben, and Ashley Casey. 2016. Cooperative Learning in Physical Education and Physical Activity: A Practical Introduction . London, UK: Routledge). Data collection : Data was collected over two school years. A minimum of 6 observations per year were carried out at each school. Students were interviewed in focus groups of three or four students. Four focus group interviews were carried out at every school each year. Data analysis: Inductive analysis and constant comparison were used for data analysis (Miles et al. 2014). Trustworthiness was enhanced by utilizing the data analysis strategies and was undertaken through the analysis of data by continually challenging the interpretations of the findings, identifying conceptual links, and uncovering key categories through frequent peer debriefing with the researchers. Findings: Four main themes for learning outcomes that allied with the five key elements of CL and SEL outcomes were: being part of a team; learning how to listen; helping and encouraging others; and, making physical education fair . Findings indicate that learning outcomes of CL in PE align and compliment SEL outcomes. In their heterogeneous, CL groups, students identified and talked about SEL skills as being central in their PE lessons. Conclusion: CL has the potential to be a successful model-based practice to develop SEL outcomes in PE. Further studies on the use of CL and other models-based practices for teaching SEL in PE could legitimize the current popular political and educational rhetoric.